Mengurai Pengalaman Positif Tamu Saat Menginap di Sheraton Senggigi Beach Resort: Bukti Dari Ulasan TripAdvisor - Setiawan, Ahmat; Sukmana, Febrian Humaidi (Jurnal Kepariwisataan Indonesia: Jurnal Penelitian dan Pengembangan Kepariwisataan Indonesia, 2023)
Customer reviews on the internet play an essential role in generating opinions in electronic Word-of-Mouth (eWOM); This review serves as an online communication tool that significantly influences the perception of the following potential user. The purpose of this study is to understand the opinions that often appear in actual customer reviews that give an Excellent and Very Good rating. This study collected 1.515 online review data from the Tripadvisor website using automated web data mining techniques. Next, we used the JMP Pro 14 software to parse and visualize the research data at the analysis stage. The data shows that the most critical customer satisfaction lies in non-physical services, namely "staff" services, where most of the reviews express the meaning of being very satisfied with the services provided by the staff. Meanwhile, in the aspect of physical attributes, there is an important note, namely the "room" aspect, where this term is used to refer to complaints of bedrooms and bathrooms that are old and dirty enough to require renewal. Physical attributes, such as pool, breakfast, beach, and restaurant, are satisfactory because they can meet customer expectations